Effect of Intelligence Tutoring System on Students' Achievement in Algebraic Expression - Tsai, Chen Chien (2007)
In this quasi experiment study, an Intelligent Tutoring System (ITS), was compared to the Computer Assisted Instruction (CAI) in tutoring students to learn the topic on Algebraic Expression. The ITS system consisted of two main structures in the architecture, the Student Model and Tutorial Model. The Student Model stores student's responses throughout the tutorial process while the Tutorial Model presents a suitable tutoring strategy to students according to their progress. In order to identify the effect of ITS on student's achievement, 62 students in one of the private school in Perak were involved in the study. The Subjects consist of two intact groups. The groups were randomly assigned as the control group and the experimental group. One of the group studied algebraic expression in a CAI learning environment, while the other were in a CAI and ITS (CAI+ITS) environment. Before the experiment began, subjects were given a pre-test on algebraic expression, together with questionnaires of learning style and attitude towards mathematics. Post-test was given by the end of the study. The study was administered in eight slots with one hour per slot. Both groups of subjects studied the algebraic expression in CAI environment at first stage of the study. After completing the first stage, subjects from CAI group went through a tutoring session with CAI, whereas subjects from the CAI+ ITS environment continue their study in ITS tutorial.